Cilostazol prevents foot ulcers in diabetic patients with peripheral vascular disease - de Franciscis, Stefano (Int Wound J, 2013)
Diabetic patients are at high risk of foot ulcerations that may lead to limb amputations with important socio‐economic impact. Peripheral vascular disease may be frequently associated in diabetes mellitus type II with its main symptom, intermittent claudication. Many studies reported the known efficacy of cilostazol in treating vascular claudication. Metalloproteinase‐9 (MMP‐9) seems to be a biochemical marker implicated in chronic wounds and in particular in diabetic foot ulcers. Cilostazol appears to have a lowering effect on MMP‐9 levels and this may suggest a beneficial effect in order to prevent or retard the onset of foot ulcer in diabetic patients. In our study, two groups of diabetic patients with peripheral vascular disease were divided into two groups according to the presence of claudication in order to receive cilostazol. Group A (31 patients without claudication) were not eligible to receive cilostazol whereas Group B (47 patients with claudication) received cilostazol administration for 24 weeks (100 mg orally twice daily). Median follow up was of 16 months. During the follow up, 4·25% of patients of Group B and 35·48% of patients of Group A (P < 0·01) showed onset of foot ulceration. Although further randomised and controlled studies are required cilostazol seems to show beneficial effects for primary prevention of diabetic foot ulcers.